Establishing a Framework for an Islamic Waqf Bank in Nigeria - Tom, Muhammad Jidda (Journal of International Conference Proceedings, 2024)
Islamic finance, grounded in Shariah principles and ethical guidelines, has emerged as a pivotal tool for socioeconomic development. Waqf, an Islamic endowment, holds significant potential to address social welfare and economic challenges. This study proposes a framework for establishing an Islamic Waqf Bank in Nigeria to drive economic growth and financial inclusion. The framework integrates the ethical principles of Waqf with modern financial practices, aiming to foster poverty alleviation, education, healthcare, and infrastructure development. Key components include a robust governance structure to ensure transparency and accountability, innovative financial products aligned with Waqf principles, and strategic focus on projects yielding sustainable community benefits. The paper also examines legal and regulatory requirements, ensuring compliance with Shariah jurisprudence and national banking laws. Challenges such as limited awareness, regulatory hurdles, and cultural misconceptions are identified, alongside mitigation strategies to enhance feasibility and sustainability. By leveraging Nigeria's socioeconomic landscape, the proposed Islamic Waqf Bank framework offers a transformative model for addressing pressing economic needs while adhering to Islamic financial ethics